New Rice for Africa (NERICA) cultivars exhibit different levels of post-attachment resistance against the parasitic weeds Striga hermonthica and Striga asiatica - Cissoko, M.; Boisnard, A.; Rodenburg, J.; Press, M.C.; Scholes, J.D. (Wiley, 2011)
Striga hermonthica and S. asiatica are root parasitic weeds that infect the major cereal crops of sub-Saharan Africa causing severe losses in yield. The interspecific upland NEw RICe for Africa (NERICA) cultivars are popular amongst subsistence farmers, but little is known about their post-attachment resistance against Striga. Here, we evaluate the post-attachment resistance levels of the NERICA cultivars and their parents against ecotypes of S. hermonthica and S.asiatica, characterize the phenotype of the resistance mechanisms and determine the effect of Striga on host biomass. Some NERICA cultivars showed good broad-spectrum resistance against several Striga ecotypes, whereas others showed intermediate resistance or were very susceptible. The phenotype of a resistant interaction was often characterized by an inability of the parasite to penetrate the endodermis. Moreover, some parasites formed only a few connections to the host xylem, grew slowly and remained small. The most resistant NERICA cultivars were least damaged by Striga, although even a small number of parasites caused a reduction in above-ground host biomass. The elucidation of the molecular genetic basis of the resistance mechanisms and tolerance would allow the development of cultivars with multiple, durable resistance for use in farmers' fields.